Pembentukan Kelompok Usaha Perhutanan Sosial di Desa Banyurip, Sragen - Yus Andhini Bhekti Pertiwi; Ana Agustina; Rezky Lasekti Wicaksono; Galuh Masyithoh; Rissa Rahmadwiati; Sigit Murhofiq (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Social Forestry is part of community empowerment, aimed at communities living in and around forests. Banyurip Village is one of the inclave villages in the Perum Perhutani KPH Surakarta teak production forest area with a high poverty rate. The Banyurip Village community has joined the Banyurip Lestari Forest Village Community Institution (LMDH Banyurip Lestari). However, LMDH Banyurip Lestari has not yet been able to play an optimal role as expected. Therefore, so cooperation between various parties is needed as an effort to empower the community, especially women, by increasing the capacity of business institutions and/or entrepreneurship through the formation of Social Forestry Business Groups (KUPS) managed by woman. Activities carried out include technical guidance on the formation of KUPS, assistance in the preparation of AD/ART and preparation of group administration. The KUPS formed is called KUPS Kembang Pilang. KUPS Kembang Pilang is led by a chairman who is assisted by a secretary, treasurer, institutional management section, area management section, and business management section. When it was founded, KUPS Kembang Pilang consisted of 26 women domiciled in Banyurip Village. In the present community services program, the articles of association (AD/ART) of KUPS Kembang Pilang was composed. KUPS Kembang Pilang members known their rights and obligations to conduct sustainable forest management towards an economically independent village.